A descriptive field research on the comparative perception of health service among selected customers: medical doctors and patient - Akşehirlioğlu, Banu (My University, 2001)
Seçilmiş Müşteriler Arasındaki Karşılaştırmalı Sağlık Hizmeti Algısı Üzerine Tanımlayıcı Bir Saha Araştırması: Doktorlar ve Hastalar Bu tanımlayıcı saha araştırması, sağlık sektöründe yer alan iki farklı grup arasındaki sağlık hizmeti algısını karşılaştırmaya çalışmıştır. Saha araştırması 100 kişisi doktor, 100 kişisi de hasta olmak üzere toplam 200 kişiden oluşmuştur. Araştırma ile, sağlık sektöründe hem sağlık hizmeti alan, hem de sağlık hizmeti veren taraflar arasında bir bağlantı kurulması da sağlanmıştır. Dikkate alınacak birkaç nokta şöyle sıralanabilir: * Sağlık hizmetinin kavramsal sınırları doktorlar ve hastalar tarafından farklı algılanabilir. Bu durum tarafların birbirlerinden beklentileri arasında bir ayırım oluşturabilir. * Doktorların mesleklerine karşı etik yaklaşımları Hekimlik Andı vasıtasıyla araştırılmaya çalışılmış ve doktorlar arasında farklı farklı yaklaşımlar olabileceği görülmüştür. Bu durum mesleklerini icra ederlerken farklı davranışlar sergilemelerine sebep olabilir. * Bu tezden hareketle doktorların ve hastaların sağlık hizmetleriyle ilgili cümlelere verdikleri yanıtların sebepleri başka araştırmalara konu olabilir.

A Descriptive Field Research on the Comparative Perception of Health Service among Selected Customers: Doctors & Patients This descriptive field research tried to compare the perception of health service between two different groups taking part in the health sector. It consisted of 100 medical doctors and 100 patients, in total 200 participants. It has established contacts with different sides involved in the health sector such as the sides that provides health service and the sides that receives health service. The main points to be considered are as follows: * Doctors and patients might understand the conceptual limits of health service differently. This might create a discrepancy between their expectations from each other. * Doctors' ethical approach to their profession has been questioned through the Medical Oath and one can say that doctors might have different approaches and such a situation might influence the way they perform while providing health service * Further detailed researches might be possible on the reasons of the replies given to the statements by medical doctors and patients
Keywords: Doktorlar Türkiye; Fiziksel hastalık ve verilen hizmetler; Sağlık Hizmetleri; Toplumsal refah sorunları